TRANSACTIONAL THEORY PERSPECTIVES ON ADOLESCENTS’ CHOICE TO MAINTAIN PREMARITAL PREGNANCY: A LITERATURE REVIEW - Putu Davina Suastiari Devi; Tience Debora Valentina (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This narrative literature review aims to explore how transactional theory can explain the perception of stress, the factors that influence it, and the choice of coping strategies among adolescents with premarital pregnancies who decide to maintain their pregnancy. Analysis was carried out on nine open-access articles published between 2019 and 2023 from PubMed and Google Scholar. The review found that adolescents perceive pregnancy as a threatening stressor. Primary appraisal is influenced by fear of social responses, concerns about the future, and the partner’s reaction. Secondary appraisal involves evaluating the responses of family, partner, community, and the adolescent’s level of religiosity. When appraised positively, adolescents adopt adaptive coping strategies such as getting married, strengthening family relationships, increasing religiosity, and accepting their circumstances. In contrast, maladaptive coping includes considering or attempting abortion, avoiding social interactions, and not accessing health services. Reappraisal occurs when adolescents eventually receive social support from their families, enabling them to interpret their pregnancy more positively.